Reflexões sobre a idéia de "sociedade civil global" e a ação política não-estatal além das fronteiras - Budini, Terra Friedrich (2010)
This research shows the diversification of the debate on global civil society and the non-state political action beyond borders in the recent International Relations literature. The interest of an increasing variety of theoretical perspectives on these issues reflects wider debates on the concepts that as the idea of global civil society have emerged in the discipline since the beginning of the 1990s. The insufficiencies of liberal-oriented literature to explain the maintenance of inequalities and power hierarchies in the world system is the background to this diversification. Part of the positive image associated to a global civil society lies on the idea that the lost of autonomy in domestic realm engendered by the globalization processes could be counterbalanced with the transnational/global activism, that is to say in the idea of reformulating the mediation between universality/particularity formalized by the constitution of modern political boundaries. The objective is establishing dialogues between these variety of perspectives and mapping these discussions, not only in relation to the actors and process directly involved in the transnational political action, but also shedding light in their intersection with the wider and more theoretical debate on the problem of borders, of mediation between domestic and international realms, and the idea of constitution of a global political field